Determination of the Elastic Constant of the Top Plate of a Cello in the Interaction with the Bridge - Paupy, Pablo Esteban (2025)
This paper aims to determine the equivalent static elastic constant of a cello’s top plate in the interactionwith the bridge. Experimental results detailing this constant are presented based on measuring the deformationand forces caused by a system of calibrated springs in similar conditions to that obtained when these forces areproduced by the action of the strings. Subsequent tests are conducted following an intervention by a luthier toadjust the sound post, with the aim of assessing the impact on the elastic constants.